Chlamydia intracellular biology, pathogenesis, and immunity - Stephens, Richard Scott;Ed (ASM Press, 1999)
Designed as a synthetic, comparative volume, this book comprehensively compares, contrasts, and integrates issues across all chlamydial species. The contributors provide a thorough review of previous research and indicate the top research needs in each area.